1995
DOI: 10.1007/bf00243909
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical differences of the lectin affinities of backbone polylactosamine structures carrying the ABO blood group antigens in papillary carcinoma and other types of thyroid neoplasm

Abstract: Endo-beta-galactosidase from Escherichia freundii cleaves linear polylactosamine structure as follows: R-GlcNAc-beta 1-3Gal-beta 1-4GlcNAc-beta 1-R' + H2O-->R-GlcNAc-beta 1-3Gal + GlcNAc-beta 1-R'. Staining with Griffonia simplicifolia agglutinin II (GSA-II) following enzyme digestion reveals the distribution of R-GlcNac-beta 1-3Gal-beta 1-4GlcNAc-beta 1-R' structures in tissue sections. In this study, the procedure was applied to formalin-fixed, paraffin-embedded tissue sections from 26 cases of papillary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…2). Such labelling patterns were also similar to those obtained with MAbs against blood group antigens, with GSA-II following endo-{3-galactosidase digestion, and with lectins (Ito et al, 1994bYokota et al, 1995). No staining with 5-D-4 was observed in neoplasms such as follicular carcinomas …”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…2). Such labelling patterns were also similar to those obtained with MAbs against blood group antigens, with GSA-II following endo-{3-galactosidase digestion, and with lectins (Ito et al, 1994bYokota et al, 1995). No staining with 5-D-4 was observed in neoplasms such as follicular carcinomas …”
Section: Resultssupporting
confidence: 79%
“…Since digestion with keratanase eliminated the 5-D-4 reactivity found in some other human tissues such as the acinar cells of the parotid and submandibular glands (Ito et al, unpublished observation), the inability of this enzyme to abolish or reduce the reactivity with 5-D-4 in carcinoma cells could not be due to an inactive or poorly active enzyme. As reported previously (Ito et al, 1994b;Yokota et al, 1995), reactivity with MAb-A, MAb-B, UEA-I, and LEA in papillary carcinomas was reduced or eliminated by prior endo-[3-galactosidase digestion (Table 3). The intensity of labelling with these reagents was also diminished or abolished by treatment with N-glycosidase F (Fig.…”
Section: Endo-~-galsupporting
confidence: 66%
“…19). As reported in previous papers (Ito et al, 1994b;Yokota et al, 1995), GSA-II rarely reacted with cancer cells without prior enzyme digestion.…”
Section: Resultssupporting
confidence: 79%
“…Since the enzyme cleaves the inner Gal~I-4GlcNAc linkage of linear poly-N-acetyllactosamine to expose terminal GlcNAc residues (Fukuda & Matsumura, 1976;Scudder et al, 1984), GSA-I1 staining combined with prior endo-~-galactosidase digestion makes it possible to demonstrate linear poly-N-acetyllactosamine structures in tissue sections. Recently, an endo-~-galactosidase digestion procedure has also been applied to the analysis of the backbone structure of blood-grouprelated antigens in human thyroid neoplasms; this revealed that the antigens are carried predominantly by poly-N-acetyllactosamine structures containing a linear domain susceptible to endo-~-galactosidase digestion (Ito et al, 1994b;Yokota et al, 1995). Although the enzyme digestion disclosed GSA-II reactivity in papillary carcinomas, such treatment elicited little or no GSA-II reactivity in other types of neoplasm (Yokota et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation